2020
DOI: 10.7717/peerj.9558
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of rain gauge sampling density for river discharge prediction using Bayesian calibration

Abstract: River discharges are often predicted based on a calibrated rainfall-runoff model. The major sources of uncertainty, namely input, parameter and model structural uncertainty must all be taken into account to obtain realistic estimates of the accuracy of discharge predictions. Over the past years, Bayesian calibration has emerged as a suitable method for quantifying uncertainty in model parameters and model structure, where the latter is usually modelled by an additive or multiplicative stochastic term. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Uncertainty assessment refers to the estimation of quantifiable uncertainties. The uncertainty from input factors (e.g., parameters and input data) can be quantified with uncertainty analysis, also called uncertainty propagation or error propagation (Crosetto et al, 2001;Heuvelink, 1998;Wadoux et al, 2020). For RS-based models, analytical techniques which are based on the law of variance propagation (Taylor, 1997) are often not suitable because these models are essentially nonlinear functions.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…Uncertainty assessment refers to the estimation of quantifiable uncertainties. The uncertainty from input factors (e.g., parameters and input data) can be quantified with uncertainty analysis, also called uncertainty propagation or error propagation (Crosetto et al, 2001;Heuvelink, 1998;Wadoux et al, 2020). For RS-based models, analytical techniques which are based on the law of variance propagation (Taylor, 1997) are often not suitable because these models are essentially nonlinear functions.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…The integration of geostatistical probability models that interpolate and simulate precipitation data in the spatial and temporal domains would be an important advancement in USSM. Studies that addressed these topics are found in Muthusamy et al (2017), Cecinati et al (2018), andWadoux et al (2020). Those approaches could also be applied to urban hydrology.…”
Section: Comparison With Recent Developments and Future Directionsmentioning
confidence: 99%